Primary securities markets Cross country findings. - Aylward, Anthony H.; Glen, Jack D. 1953-. (Washington, D.C. World Bank, 1999)
Annotation IFC Discussion Paper No. 39. During the period 1980-95, the level of activity increased dramatically for funds raised domestically via issues of debt and equity securities in public capital markets in 32 countries. There were also substantial differences in the level of activity across markets and countries. This paper examines aggregate domestic primary capital market activity in a cross section of countries, including 24 emerging markets. It defines exactly how important a role financial markets have played in raising capital for investment. In this pioneering work, the authors compile aggregate data on primary market activity for a recent period of time, which allows them to quantify the size of the markets and how they have evolved over time. Through their analysis, the authors document the rapidly increasing importance of primary capital markets in many developing countries, where, relative to GDP, these markets now source as much private capital as their developed country counterpart.
Keywords: Capital market